Development of Inquiry-Based Learning Tools to Enhance Students' Learning Interest and Conceptual Understanding in Mathematics (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study aims to develop an inquiry-based mathematics learning tool that is valid, practical, and effective in enhancing students’ learning interest and conceptual understanding. Unlike previous studies, this research focuses on the development of inquiry-based learning tools to enhance learning interest and conceptual understanding of mathematics among elementary school students, specifically within the context of education in Lombok. The research employed a Research and Development (R&D) approach using the 4-D model (Define, Design, Develop, Disseminate). The participants consisted of 26 fourth-grade students at SDN 4 Pringgabaya, East Lombok. The instruments used included learning material validation sheets, teacher and student response questionnaires, a learning interest questionnaire, and a conceptual understanding test. Data were collected through document analysis, questionnaires, and tests, then analyzed descriptively using percentage categories and N-gain Test. The findings revealed that all components of the developed instructional materials were rated “very valid” by experts. During the implementation phase, the materials were rated “very practical” (86.67%) based on teacher responses. Post-intervention data indicated that 88.46% of students reached the “very high” category of learning interest, while 81% met the minimum mastery criteria for conceptual understanding. The results of the N-Gain test show an average N-Gain value of 0.7166, which falls into the high category. This indicates an improvement in students' conceptual understanding. These results confirm that the inquiry-based learning materials developed in this study are valid, practical, and effective in improving students’ interest and conceptual understanding in mathematics. The success of this learning tool can make a contribution to educational policies at the regional level, with relevance to the development of an inquiry-based curriculum approach that can be more widely implemented in elementary schools.